To Express or to End? Personality Traits Are Associated With the Reasons and Patterns for Using Emojis and Stickers - Liu, Siying; Sun, Renji (Frontiers in Psychology, 2020)
Emojis and stickers are becoming increasingly popular in computer mediated communications. The present study examined the associations between personality traits and people’s reasons and patterns for using both emojis and stickers. Participants (n= 312) completed three on-line questionnaires assessing shyness, the Big Five personality traits and why and how they used emojis and stickers. Results revealed that shyness, neuroticism, extraversion and agreeableness were correlated with different reasons of usage. Moreover, some participants exhibited a tendency to adjust frequency of usage depending on who the target person was and whether they were in a private or group chat. People who showed such tendencies were found to differ in personality with those who did not. Some differences in usage patterns were also observed between emojis and stickers. Together, the present study sheds more insights into how emojis and stickers can help people with different personality traits to achieve different purposes in their daily communication.